Taxing corporate income in the 21st century - Auerbach, Alan J (Cambridge University Press, 2007)
In this book most of the top stars of public finance economics grapple with a series of issues surrounding the taxation of corporate income. These include, among others, the reactions of corporations to changes in the corporate tax rate, tha reactions of the market to changes in the tax on dividends, and the efforts of corporations ( by choosing their location, by their debt-finance decisions, and by other means) to reduce their tax liabilities